Analysis of ITO/a-Si:H(p)/a-Si:H(i)/c-Si(n)/Al HIT (Heterostructure with Intrinsic Thin Layer) solar cell performances. - Igor Levi Satriani; Rahmawati Munir; Adrianus Inu Natalisanto; Dadan Hamdani (Faculty of Engineering, Universitas Tanjungpura, 2023)
Numerical simulation on HIT (Heterostructure with Intrinsic Thin Layer) solar cell using hetero-structure ITO/(p+)a-Si:H/(i)a-Si:H/(n)c-Si/Al solar cell has been done using AFORS-HET (Automate For Simulation of Heterostructure) software. The purpose of this study is to provide validation as well optimization model of solar cell enhanced performances. Data analysis shows a significant increase on solar power generation. An intrinsic thin layer given between the hetero-interface to reduce defect properties on solar cell structure. The optimization using an optimal value of acceptor-donor doping, dangling-bond defects ( ), thin conductive oxide work function ( ), and other input shows a reducing recombination-rates, as a validation Figure of Merits (FOMs) data reach a maximum efficiency value at 23,67% ( = 634,2 mV; = 51,2 mA/cm2; = 72,91%, this result achieved on peak data such = 5,2 eV, Na (doping) = 5.0 x 1019 cm-3, = 1.0 x 1018 cm-3, (interface defect) = 1.0 x 1010 cm-3. The results obtained from this simulation produce a number of optimum parameters that can be followed up experimentally to obtain better solar cell performances.